1980
DOI: 10.1128/aac.18.5.651
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibilities of clinical isolates of Serratia marcescens to newer cephalosporins, alone and in combination with various aminoglycosides

Abstract: We examined 100 clinically significant isolates of Serratia marcescens for susceptibility to newer cephalosporin and cephamycin antibiotics, alone and in combination with various aminoglycosides. Moxalactam and cefotaxime were the most effective agents; all isolates were inhibited by 25 and 50 ,ug/ml, respectively. All strains were susceptible to amikacin at concentrations safely achievable in serum, whereas gentamicin, netilmicin, and tobramycin inhibited 63, 63, and 16% of the isolates, respectively. Moxalac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
1990
1990

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Antagonism with azlocillin-cefotaxime was observed with 11% of the Enterobacteriaceae. [10][11][12]14). Although antagonism was not observed in the present study, it has been occasionally observed with both types of combinations against Enterobacteriaceae and P. aeruginosa (3,5,6,8,11,14).…”
mentioning
confidence: 40%
“…Antagonism with azlocillin-cefotaxime was observed with 11% of the Enterobacteriaceae. [10][11][12]14). Although antagonism was not observed in the present study, it has been occasionally observed with both types of combinations against Enterobacteriaceae and P. aeruginosa (3,5,6,8,11,14).…”
mentioning
confidence: 40%
“…Most of the strains reported have been highly resistant to the currently available antibiotics, except to a few aminoglycosides, including gentamicin and amikacin (4,18,19). Recently, however, increasing numbers of reports have pointed out the rise in epidemics due to strains resistant even to gentamicin or to amikacin (3,5,6,12,15,18), thus posing difficulties in the control of S. marcescens infections.…”
mentioning
confidence: 99%
“…Several investigators have shown notable in vitro synergy between amikacin and semisynthetic penicillins or cephalosporins against highly resistant Pseudomonas aeruginosa and Serratia marcescens (12,13,15), as well as against multiply resistant strains of Enterobacteriaceae. Using the checkerboard technique, Jones and Packer (7) found that the combinations of amikacin plus cefotaxime or moxalactam produced synergism against 67 and 54%, respectively, of their Enterobacteriaceae strains, whereas D'Alessandri and co-workers (2) demonstrated synergism between cephalothin and amikacin for 26 of 38 Klebsiella isolates (68%).…”
Section: Discussionmentioning
confidence: 99%